STEM-27. LEVERAGING FUNCTIONAL GENETIC DEPENDENCIES IN TREATMENT-REFRACTORY GLIOBLASTOMA. (11th November 2019) - Chokshi, Chirayu; Tieu, David; Brown, Kevin; Venugopal, Chitra; Kuhlmann, Laura; Ignatchenko, Vladimir; Tong, Amy; Chan, Katherine; Savage, Neil; Subapanditha, Minomi; McKenna, Dillon; Lazo, John; et al.
Abstract: As the most common primary brain tumor in adults causing death, Glioblastoma (GBM) remains a therapeutic challenge. Unchanged for almost two decades, standard therapy is ineffective at preventing disease relapse with a median patient survival of < 15 months. Stem cell-like subpopulations of tumor cells, known as brain tumor initiating cells (BTICs), evade standard therapy and lead to relapse. Whereas previous studies largely focus on pre-treatment primary GBM (pGBM), we conducted a panel of genome-wide CRISPR-Cas9 gene knockout screens to determine modulators of treatment resistance and de novo genetic vulnerabilities arising at disease recurrence. Using our in vitro model of conventional therapy, we identified genes modulating sensitivity and resistance to Temozolomide and/or radiation therapy in patient-derived pGBM BTICs. Genes modulating sensitivity belong to Fanconi anaemia nuclear complex, interstrand cross link repair, and regulation of stem cell maintenance and differentiation. Following in vitro validation of gene knockouts conferring treatment sensitization in multiple pGBM BTIC lines, we continued to conduct the first genome-wide CRISPR-Cas9 screens in patient-derived rGBM BTICs. Focusing on genetic vulnerabilities arising de novo at disease relapse, we introduce the context-specific role of protein tyrosine phosphatase 4A2 (PTP4A2) in rGBM. Genetic knockout or small molecule targeting of PTP4A2 leads to a context-specific vulnerability of rGBM self renewal capacity and in vivo tumorigenecity. To continue our analysis of treatment-refractory GBM and overcome intertumoral heterogeneity, we conducted genome-wide CRISPR-Cas9 gene knockout screens and whole cell proteomics on patient-matched pGBM and rGBM BTICs. With >1000 differentially essential genes, combined functional genetic and proteomic analyses implicates genes involved in mRNA splicing, nucleotide metabolism, and activation of gene expression by sterol regulatory element-binding protein. Together, our functional genetic approach elucidates novel genes regulating treatment resistance and disease recurrence in GBM.